Salivary Biomarkers in Periodontitis Patients: A Pilot Study - Sarah Reddahi; Amal Bouziane; Sana Rida; Houssain Tligui; Oumkeltoum Ennibi (International Journal of Dentistry)
Background and Objective. Periodontal disease is a chronic inflammatory condition, involving the destruction of both soft and hard tissues in the periodontal region. Advances in diagnostic research are moving toward methods whereby the periodontal risk can be identified and quantified by objective measures using specific inflammatory markers that can be correlated to the severity of the disease. The purpose of this study was to evaluate salivary concentrations of IL-1β, IL-6, MMP-8, and IL-10 in healthy and periodontitis patients and to assess the association between these biomarkers levels and clinical parameters in a Moroccan population. Materials and Methods. Forty subjects were included: 10 periodontally healthy subjects and 30 periodontitis patients. Periodontal examination and saliva sampling were performed in all patients. Levels of salivary cytokines including IL-1β, IL-6, MMP-8, and IL-10 were evaluated by a sandwich ELISA test kit. Data were analyzed by SPSS for Windows. Results. Regarding individual biomarkers, IL-1β, IL-6, and MMP-8 levels were significantly higher in periodontitis patients (p≤0.001, p<0.05, respectively). The concentration of these proteins in saliva showed a significant association with gingival index and pocket depth measurements and may reflect the clinical status of healthy and diseased periodontium. However, no significant differences were observed for the IL-10 component. Conclusion. IL-1β and IL-6 concentrations were statistically higher in periodontitis patients and may be used as potential tools in periodontitis diagnosis.